Inter-comparisons of Arctic snow depth products - Li, Mengmeng; Ke, Changqing; Cheng, Bin; Ma, Jianwei; Jiang, Huiwei; Shen, Xiaoyi (Taylor & Francis, 2024)
Applying ICESat-2 and CryoSat-2 freeboards, the Arctic snow depth (ISCS) was obtained from October 2018 to April 2022. The results were assessed using Operation Ice Bridge (OIB) and Multidisciplinary Drifting Observatory for the Study of Arctic Climate (MOSAiC) in situ observations and compared with frequently used remote sensing (AMSR-E/AMSR2), climatology (modified W99 snow climatology data; MW99), and modelled (Pan-Arctic Ice Ocean Modelling and Assimilation Systems; PIOMAS) snow products. The ISCS snow depth exhibited high correlations (r = 0.67) and small mean bias (0.01 ± 0.06 m) against OIB results. We found good correlations (statistically significant) between MOSAiC and all snow depth products, except for MW99. Mean and absolute biases between ISCS and MOSAiC in situ observations were 0.01 ± 0.06 and 0.04 ± 0.04 m, respectively. The ISCS revealed clear spatial distribution from the Canadian Arctic Archipelago to open sea areas. In contrast, the PIOMAS snow depth revealed weak autumn variation, whereas the MW99 snow depth yielded distinct seasonal variability but a weak interannual change. Snow depth in October showed large differences among the various products, from which the AMSR topped the snow depth in the first-year ice region, while MW99 had the highest values for the multiyear ice zone.